2014
DOI: 10.1007/s11481-014-9558-9
|View full text |Cite
|
Sign up to set email alerts
|

The Calcineurin Inhibitor Ascomicin Interferes with the Early Stage of the Epileptogenic Process Induced by Latrunculin A Microperfusion in Rat Hippocampus

Abstract: Latrunculin A microperfusion in rat hippocampus has shown to be an effective model of acute and chronic seizures for neurochemical studies. The intervention over early synaptic plasticity changes after the epileptogenesis onset represents a big challenge on the design of a suitable therapy to impair the epilepsy development. We previously suggested that receptor location might be essential for controlling neuronal excitability, and that disruption of local cytoskeletal dynamics followed by drastic changes in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 64 publications
(90 reference statements)
1
9
0
Order By: Relevance
“…These results are consistent with our observations in rats. [27] Taken together with the effect of the increase in extracellular glutamate concentrations on latrunculin A pre-treated mice reported here and the previously reported results in rats [20] , they suggest that actin depolymerization might be not only a consequence but also a cause of epileptic seizures.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These results are consistent with our observations in rats. [27] Taken together with the effect of the increase in extracellular glutamate concentrations on latrunculin A pre-treated mice reported here and the previously reported results in rats [20] , they suggest that actin depolymerization might be not only a consequence but also a cause of epileptic seizures.…”
Section: Discussionsupporting
confidence: 82%
“…[9] Alterations in several actin-related proteins, such as acidic calponin [29] and calpain [30] have been linked to epileptic seizures in different experimental models. We have recently shown that latrunculin A microperfusion has a significant effect on components of the MAPK signaling pathways such as ERK 1/2 and pp38 [27] . Substantial evidence suggests the involvement of actin cytoskeleton in the excitability upregulation of postsynaptic neurons resulting from an increase in glutamate excitatory action [31] .…”
Section: Discussionmentioning
confidence: 99%
“…22 The beneficial effect of the introduction, as part of some refractory epilepsy therapies, of compounds like corticosteroids, immunoglobulins and monoclonal antibodies (Rituximab, Efalizumab and Natalizumab) or immunosupressors (Cyclosporine A, Tacrolimus and Rapamycin), confirms the important influence on epileptogenesis of this associated processes and thus postulating new molecular targets on the initiated immune/inflammatory cascades. 19,24,29 On the other hand, it is well known that glial cells play an important role in generating seizures by modulating synaptic transmission and, in the long term, contributing to the epileptic process by inducing inflammatory milieu around neurons. Particularly, astrocytes and microglia, are considered key players on initiating this inflammatory response after a brain insult.…”
Section: Targeting Immunity/inflammation Mechanisms and Glial Responsementioning
confidence: 99%
“…This accumulation of glutamate in extracellular areas, in addition to the previously described changes on expression and redistribution pattern of excitatory glutamate receptors to the extrasynaptic compartment on the cell membrane, would facilitate the synchronization of hyperexcitable networks as the main consequence of brain circuitry rearrangement after the epileptogenic insult. 8,19 On the same line, Neuropeptides are signaling molecules participating in the modulation of synaptic transmission. These peptides are released after neural excitation in the extracellular space and exert their action on G-protein coupled receptors pre and postsynaptically.…”
Section: Targeting Immunity/inflammation Mechanisms and Glial Responsementioning
confidence: 99%
See 1 more Smart Citation